A multi-responsive molecular switch based on a diarylethene derivative containing dinitrobenzenesulfonic amide groups. (January 2017) - Hu, Guo-Fei; Cheng, Hong-Bo; Niu, Jia-Liang; Zhang, Zhan-Hui; Wu, Hai-Chen
Abstract: Diarylethene derivatives-based multi-responsive molecular switches are indispensable for application to sensors for biological and materials sciences. The constructing of molecular switches that can respond to sulfur compounds remains a challenge. In this work, we report the design and syntheses of a new DAEs-based molecular switch3 using two strongly electron-withdrawing 2, 4-dinitrobenzenesulfonyl groups as functional groups and bisthienylethene perfluordiarylethene2 as the photoswitching trigger. The new molecular switch3 exhibits prominent photochromism in solution. More importantly, among various sulfur compounds, molecular switch3 showes specific responses toward benzenethiol and hydrosulfide ions. Highlights: Dinitrobenzenesulfonyl groups successfully connected to diarylethene backbone. The formed molecule showed prominent photochromism in solution. The specific responses toward benzenethiol and hydrosulfide ions.